1991
DOI: 10.1037/0022-0167.38.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with perceived career options in American Indian, White, and Hispanic rural high school students.

Abstract: Betz and Hackett's (1981) career self-efficacy model was extended using an ethnically mixed (White, Hispanic, American Indian) rural high school population (467 girls and 426 boys). A modified form of Betz and Hackett's interest and self-efficacy instrument was used as well as measures of ethnicity, socioeconomic status, stressful life events, and self-esteem. Gender differences were observed in interest and self-efficacy estimates for same-gender and cross-gender occupations, marked by boys' restricted consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 23 publications
2
60
0
1
Order By: Relevance
“…ethnic d.ifferences in the occupational self-efficacy of American racial! ethnic minority students (Hackett, Betz, Casas, & Rocha-Singh, 1992;Lauver & Jones, 1991;Noble, Hackett, & Chen, 1992;Post, Stewart, & Smith, 1991;Rotberg, Brown, & Ware, 1987). Four of these studies are addressed in this section; the fifth ) is discussed in the section describing research on the links between self-efficacy and academic achievement.…”
Section: Culture and Occupational Self-efficacymentioning
confidence: 96%
See 1 more Smart Citation
“…ethnic d.ifferences in the occupational self-efficacy of American racial! ethnic minority students (Hackett, Betz, Casas, & Rocha-Singh, 1992;Lauver & Jones, 1991;Noble, Hackett, & Chen, 1992;Post, Stewart, & Smith, 1991;Rotberg, Brown, & Ware, 1987). Four of these studies are addressed in this section; the fifth ) is discussed in the section describing research on the links between self-efficacy and academic achievement.…”
Section: Culture and Occupational Self-efficacymentioning
confidence: 96%
“…However, for all students, occupational self-efficacy was significantly predictive of interest in math/ science occupations (accounting for 39% of the variance in interests), indicating the possibility of an indirect effect of self-efficacy, through interests, on the range of alternatives considered by these students. Lauver and Jones (1991) investigated racial/ethnic and gender differences in the occupational self-efficacy of ninth-and eleventh-grade rural high school students. Native American students expressed lower confidence in their abilities than Anglo or Hispanic students.…”
Section: Culture and Occupational Self-efficacymentioning
confidence: 99%
“…We observed that the male Hoffmann et al / Career Barriers for Native Americans 41 students were considering a more limited range of possible careers than female students. In an earlier quantitative study, Lauver and Jones (1991) found that Native American boys appeared restricted in the consideration of cross-gender careers. They also found that Native Americans showed lower self-efficacy for many careers than others in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of EDA is to find patterns in the data that allow researchers to build rich mental models of the phenomenon being examined. Examining the Feingold (1994) and Lauver and Jones (1991) data, we found EDA useful when there is little explicit theoretical background to guide prediction and the first stages of model building is desired. Examining the Paap and Johansen data, we also saw that, even when a priori hypotheses exist, EDA can perform a valuable service by providing rich descriptions of the data that can inform the research whether their mental models are even close enough to the underlying data patterns to consider CDA.…”
Section: Conclusion: Psychological Methods and Edamentioning
confidence: 99%
“…A bivariate structure of the table is suggested that offers detail about the size of effects well beyond noting the ethnicity with the highest options in each of the six significant chi-square tests reported by Lauver and Jones (1991). In sharp contrast to most applications of CDA, detailed analysis of residuals was used both to assess the model and to understand the data by examining their departure from the model.…”
Section: Building a Two-way Fitmentioning
confidence: 99%